FILSAFAT ILMU SEBAGAI LANDASAN PENGEMBANGAN ILMU PENDIDIKAN - Setya Widyawati (Institut Seni Indonesia Surakarta, 2013)
The philosophy of science clarify the existence of science to the other science that requiresknowledge as a medium of thinking and means of scientific communication. These are language,logic, mathematics, statistics, and other data analysis techniques. Specifications and independencyscience faced by the increasing number problems that can not be answered by science, therefore,philosophy appears as the answer. Philosophy gives an explanation or an answer onthat problemssubstantial and radical, while the science continues to develop it self- in its limit , while still radicallycriticized, process or the interaction basically is a field of philosophy of science. Philosophy ofscience therefore can be put as an attempt to bridge the gap between the philosophy and science,so that science does not despise the philosophy, and the philosophy does not see science as asuperficial understanding of nature . Reality is “what is naturally “ or existence , while the appearanceis that “artificially real“. Also how the relationship to both with subject /human. Epistemology isconsidered synonymous with the theory of knowledge. At the present time theory of knowledgecan not be ignored. Epistemology of education science related to know how science educationobtaining gain processing, what is the procedure to get the true scientific knowledge. Axiologiyrelated to what is the advantages of science education, what ethical relationship with science andits application science education in daily life .